2016
DOI: 10.1016/j.marenvres.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous hitchhikers? Evidence for potentially pathogenic Vibrio spp. on microplastic particles

Abstract: The taxonomic composition of biofilms on marine microplastics is widely unknown. Recent sequencing results indicate that potentially pathogenic Vibrio spp. might be present on floating microplastics. Hence, these particles might function as vectors for the dispersal of pathogens. Microplastics and water samples collected in the North and Baltic Sea were subjected to selective enrichment for pathogenic Vibrio species. Bacterial colonies were isolated from CHROMagar™Vibrio and assigned to Vibrio spp. on the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
372
2
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 735 publications
(439 citation statements)
references
References 83 publications
13
372
2
16
Order By: Relevance
“…on marine plastics conclusively confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF MS) [60]. In their study, Kirstein et al [60] identified V. parahaemolyticus, V. fluviales, and V. alginolyticus on microplastics from the North Sea. Apart from V. alginolyticus, these species were also found on plastics collected in the brackish Baltic Sea.…”
Section: Examples Of Microbial-microplastic Interactions In Freshwatementioning
confidence: 93%
“…on marine plastics conclusively confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF MS) [60]. In their study, Kirstein et al [60] identified V. parahaemolyticus, V. fluviales, and V. alginolyticus on microplastics from the North Sea. Apart from V. alginolyticus, these species were also found on plastics collected in the brackish Baltic Sea.…”
Section: Examples Of Microbial-microplastic Interactions In Freshwatementioning
confidence: 93%
“…For example, the colonization of MPs with microbes and the adsorption of biopolymers increase the nutritional value and improve the "taste" making them more attractive for biota. In contrast, the colonization of MPs with pathogens [87] and toxic algae/bacteria might induce infections/chemical toxicity or avoidance of "bad tasting" MPs. Additionally, biofouling was shown to affect the fate of MPs by changing the particle properties (e.g., density).…”
Section: Biofilm-related Impactsmentioning
confidence: 99%
“…However, the indirect effects of PMD on microbial processes, pathogen transmission, and disease emergence are less well-known. There is evidence of diverse microorganisms, including notable human, fish and bivalve pathogens, such as some Vibrio species, living in the microbial community that is specifically enriched on PMD (Kirstein et al, 2016;Harrison et al, 2018). Yet, the virulence and disease dynamics of these pathogens hitching a ride on PMD are unknown (Keswani et al, 2016;Quero and Luna, 2017), and in this regard, a key research question moving forward would be: what is the role of PMD, particularly microplastics ingested by marine biota (clams, corals, fish, mussels, oysters, etc.…”
Section: A Commentary Onmentioning
confidence: 99%